The hypothesis of Early Home Oxygen Therapy (EHOT) in sickle cell crisis - Fakunle, Babatunde (Journal of Global Medicine, 2025)
The article by Omoigui (1) presents a thought-provoking perspective on the management of sickle cell crisis, focusing on the potential of a simple, yet overlooked, intervention: concentrated oxygen therapy during the "golden half hour." This commentary offers a constructive evaluation of the article’s central thesis and its potential implications. The central hypothesis is that when triggers induce haemoglobin polymerisation, resulting in sickling and increased rigidity of erythrocytes, the sickle cells formed can be reversed with early administration of concentrated oxygen. This time-dependent use of oxygen prevents reversible sickle cells (RSC) from progressing to irreversible sickle cells (ISC), thereby preventing the end-organ sequelae of sickle cell crises. While the proposal is promising, a comprehensive appraisal must address several critical limitations. These points are essential for guiding future research and clinical application. There is limited patient data, as the hypothesis has been tested only on a small sample size of seven patients over a 20-year period. This is insufficient data to establish a causal relationship or justify a significant change in clinical guidelines. The safety of home oxygen use needs to be addressed, as does the role of oxygen therapy in exacerbating ischaemia-reperfusion injury. Omoigui’s article (1) is potentially an essential contribution to the field of sickle cell disease management. It serves as a vital call to re-evaluate our foundational assumptions about crisis management and prevention, and it should stimulate a new wave of studies dedicated to validating this promising approach. The priority is to test the hypothesis in a large sample of patients with measurable objective markers, both before and after the initiation of early home oxygen therapy.